Rupture of rudimentory horn pregnancy with catastrophic haemorrhage - Joshi, Lalita (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A 20 yrs primigravida who had attended antenatal clinic 2 weeks back, presented with shock acute abdomen and jaundice at 18 weeks of gestation. Clinically their was evidence of free fluid in the abdominal cavity. Ultrasonography showed dead fetus with haemoperitoneum which was massive at laparotomy. There was rupture of the rudimentary horn on the left side. This was attached to the normal uterus with the broad band. The placenta and fetus in a sac was lying in the peritoneal cavity. The tubes and ovaries on both sides were found normal. Key Words: Rudimentary horn, hemoperitoneum, acute abdomen in second trimester. doi:10.3126/njog.v2i2.1461 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 75 - 77